Crown Prince of Pahang officiates Masjid al-Jazari and joins Iftar Jama’ie with 2,000 UMPSA community - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 17 March 2025 – His Royal Highness the Crown Prince of Pahang, Tengku Hassanal Ibrahim Alam Shah Ibni Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah, who is also the Pro-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), officiated the UMPSA mosque, naming it Masjid al-Jazari, after the renowned 12th-century Muslim scientist and engineer.